Life in the old cloth [videorecording (DVD)] - Phillips, Xander; Gilbert, Caroline; McClusky, James (Rusalka Pictures, 2025)
The war ended long ago but one soldier never stood down. Lance Corporal Charles William Morris was lost to war in 1943. Decades later, he awakens in the present day confused, scarred, and still bound by duty. When he is discovered in a crumbling old house by his granddaughter Mary and a curious urban explorer named Ewan, the soldier believes his mission is not yet over.